Penerapan Sistem Otomasi Perpustakaan Untuk Meningkatkan Kinerja Pustakawan di Perpustakaan Pusat Universitas Warmadewa - Adnyana Putri, Ni Putu Ratih; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2017)
The purpose of this research is to know the scope of automation system applied in Warmadewa University Central Library and the influence of the implementation of library automation system to the performance of librarian. This research use descriptive qualitative research technique. The subjects of this study are all librarians at Warmadewa University Central Library, with the number of population are 7 librarians and the number of samples corresponding to the total population of librarians at Warmadewa University Central Library. Data collection techniques used were interviews, direct observation and questionnaires. Data collection techniques used were interviews, direct observation and questionnaires. The results of this study show that the library automation system has good system quality and easy to use. The library automation system is capable of improving the performance of librarians, especially in terms of service to librarian users and library collection processing. Keywords: librarian performance, library, automation system